Identification of The Same and The Major Components in Zingiber amaricans BL., Zingiber aromaticum Val. and Zingiber zerumbet (L.) Smith Rhizomes Essential Oils from Jumapolo Karanganyar Central Java Indonesia - Sri Retno Dwi Ariani; Nurul Septiana; Septa Falentina (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
The aim of this research was to know about the same and the major essential oils components in bitter ginger (Zingiber amaricans BL.), fragrant ginger (Zingiber aromaticum Val.) and shampoo ginger (Zingiber zerumbet (L.) Smith) rhizomes from Karanganyar Central Java Indonesia. The steps of this research were prepared samples, extracted with steam destillation methode and identificated essential oil components of samples with Gass Chromatography-Mass Spectrophotometry (GC-MS) method. The same components between Z. amaricans BL., Z. aromaticum Val., and Z. zerumbet  (L.) Smith were zerumbone, α-humulene, β-selinene dan (-)-caryophyllene oxide. The mayor constituent in Z. amaricans BL., Z. aromaticum Val., and Z. zerumbet  (L.) Smith oils were zerumbone. Z. zerumbet  (L.) Smith oil presented the highest quantity of zerumbone (77.62%).